2009
DOI: 10.1152/ajprenal.90622.2008
|View full text |Cite
|
Sign up to set email alerts
|

Acute-phase response protein serum amyloid A stimulates renal tubule formation: studies in vitro and in vivo

Abstract: Kelly KJ, Kluve-Beckerman B, Dominguez JH. Acute-phase response protein serum amyloid A stimulates renal tubule formation: studies in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 27 publications
(36 reference statements)
2
41
0
Order By: Relevance
“…With regard to intestinal homeostasis, Ivanov et al (51) SAA is also able to induce renal tubule formation in vitro with the in vivo expression of SAA associated with tubule generation in embryonic or ischemic kidneys (52). We demonstrate that sustained IL-22 exposure, delivered by adenovirus (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…With regard to intestinal homeostasis, Ivanov et al (51) SAA is also able to induce renal tubule formation in vitro with the in vivo expression of SAA associated with tubule generation in embryonic or ischemic kidneys (52). We demonstrate that sustained IL-22 exposure, delivered by adenovirus (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…Current work has demonstrated a strong renal inflammatory component following AKI (14), and some have reported that mediators of inflammation could also be beneficial in AKI (4). The notion that components of inflammation can be protective is supported by our work showing that serum amyloid A protein (SAA), a classic component of the acutephase reaction linked to inflammation, also promotes tubulogenesis (15). With the availability of bone marrow-derived stem cells, infusion of exogenous potential renal cell precursors became possible, and attempts have been made to replace and renew the damaged renal cell populations.…”
mentioning
confidence: 65%
“…Thus the benefit from stem cell infusions was thought to be secondary to a paracrine action rather than structural replacement by a cell population of exogenous origin (2,26). In this work, we report that NRK52E cells reprogrammed to express tubulogenic mouse SAA1.1 (15) formed tubules in vitro and promoted recovery when these reprogrammed cells were injected into rats with AKI.…”
mentioning
confidence: 73%
See 2 more Smart Citations